Reducing the Waste of Active Power by Choosing the Right Reactive Power Source (Texas Journal of Engineering and Technology, 2023)
The research work on the correct selection of the place of installation of the reactive power source and reduction of the waste of active power, taking into account the consumption of reactive power in consumers, is covered.